Direct synthesis of Au/TiO2/graphene composites and their application for degradation of various organic dyes - Jeong, Gyoung Hwa; Kim, Sang Wook (Applied Chemistry for Engineering, 2020)
In this research, we synthesized Au/TiO2/graphene composites using ionic surfactants for the exfoliation of graphite layers, directly. In the graphene composite, TiO2 with thin nanosheet shapes was distributed on the graphene surface and Au nano-particles with less than 10 nm sizes were evenly distributed on the surface of the TiO2 nanosheets. The Au/TiO2/graphene composite was then applied to the photodegradation of various dyes such as methylene blue, methylene orange and rhodamine 6G, and B. Among them, the methylene blue showed the most excellent photodegradation activity (91.6%) while the rhod-amine B exhibited 31.0%.
Keywords: Au/TiO2/graphene; Graphite; Organic dye; Photodegradation